The moral forming of children of school age is in co-operation of family and school - Короленко, Віктор (Educational Dimension, 2015)
Korolenko V. L. The moral forming of children of school age is in co-operation of family and school. In the article importance of the moral forming of children of school age is examined on the basis of pedagogical achievements of humanity, using in the process of education of national, domestic pedagogics and pedagogics of other people’s experience. Ability of the effective use of pedagogical knowledges of different people is underlined. The importance of ability of teachers to use the personal moral knowledge and experience in co-operating with the children of school age in general educational establishments (conversation, elucidation, personal example), maintenance them in vital situations is specified.